PENGEMBANGAN BUKU SAKU HOMESTAY ASEAN STANDARD BERBASIS CLEANLINESS, HEALTH, SAFETY, AND ENVIRONMENTAL SUSTAINABILITY (CHSE) SEBAGAI MEDIA PENGABDIAN KEPADA MASYARAKAT PENGELOLA HOMESTAY DI DESA CISAAT JAWA BARAT - Fifi Trisnawati; Prastiti Laras Nugraheni; Nurlaila Abdulah Mashabi; Mulyati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2021)
Abstract The purpose of developing this Cleanliness, Health, Safety, and Environmental Sustainability (CHSE) pocket book this is as a medium education in devotion the community tourist village Cisaat homestay in management, West Java. It has to be done to encourage to recover the tourist village affected areas pandemic disease coronaviruses (covid-19). The development of the CHSE pocket book uses the ADDIE (Analyze, Design, Development, Implementation, Evaluation) method and is validated by material experts, media experts, and 16 respondents. The results of the feasibility test from material experts showed an average value of 4.7; media experts obtained an average score of 4.8; and the final results of field test validation (respondents) get an average value of 4,325; based on the results of the validation test, this pocket book is in the very feasible category. After going through the validation stage, this media was implemented in community service activities with a target sample of 23 homestay managers using the Quasi one group pretest-posttest design method. The results of pretest and postest show an increase understanding homestay management related homestay management based chse which has indicated by the increase in the value the average of 71,7 to 78.69. The increased understanding of CHSE-based homestay management through the CHSE pocket book is expected to be able to implement CHSE in Cisaat Tourism Village. The increasing understanding related homestay management based chse through a pocket book is expected to homestay management can start applying the standards chse in tourist village cisaat so that it can be raise public confidence and interest in traveled in tourist village Cisaat. Abstrak Tujuan pengembangan buku saku Cleanliness, Health, Safety, and Environmental Sustainability (CHSE) ini adalah sebagai media edukasi pada pengabdian masyarakat pengelola homestay di Desa Wisata Cisaat, Jawa Barat. Hal tersebut dilakukan untuk mendorong upaya pemulihan desa wisata yang terdampak pandemi corona virus disease (covid-19). Pengembangan buku saku CHSE menggunakan metode Research and Development (RnD) dengan model pengembangan ADDIE (Analyze, Design, Development, Impelementation, Evaluation) dan di validasi oleh ahli materi, ahli media, dan 16 orang responden. Hasil uji kelayakan dari ahli materi menunjukkan nilai rata-rata 4,7 ; ahli media diperoleh nilai rata-rata 4,8 ; dan hasil akhir validasi uji lapangan (responden) mendapatkan nilai rata-rata 4,325; berdasarkan hasil uji validasi media buku saku ini berada pada kategori sangat layak. Setelah melalui tahap validasi, media ini diimplementasi pada kegiatan pengabdian kepada masyarakat dengan target sampel 23 pengelola homestay dengan menggunakan metode Quasi one group pretest-postest design. Hasil pretest dan postest menunjukkan adanya peningkatan pemahaman pengelola homestay terkait pengelolaan homestay berbasis CHSE yang ditunjukkan dengan meningkatnya nilai rata-rata dari 71,7 menjadi 78,69. Analisis statistik menggunakan Uji wilcoxon menunjukkan nilai 0,008 yang artinya terdapat perbedaan yang signifikan antara pretest dan postest. Meningkatnya pemahaman terkait pengelolaan homestay berbasis CHSE melalui buku saku CHSE diharapkan pengelola homestay dapat menerapkan CHSE di desa wisata cisaat sehingga dapat membangun kepercayaan masyarakat dan meningkatkan minat wisatawan dalam berwisata di Desa Wisata Cisaat.